2005
DOI: 10.1097/01.mol.0000174152.76554.d6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of cascade testing for the detection of familial hypercholesterolaemia

Abstract: Current data support the implementation of cascade testing for familial hypercholesterolaemia as being feasible and cost-effective, but national implementation is limited to a small number of countries. Funding and the infrastructure to support it may be the major stumbling blocks in implementing this technique in many countries. Concerns about the ethics of carrying out cascade testing, and the potential psychological damage of DNA testing, appear to have been largely addressed for familial hypercholesterolae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…All patients had a molecular diagnosis using established techniques [23][24][25][26][27] or fulfilled the criteria of hmzFH. 23 All patients' charts were reviewed using preestablished criteria. Anthropometric, clinical data, time of diagnosis, initiation of treatment, duration of specific treatments were collected, and all pertinent surgical reports were reviewed.…”
Section: Study Subjectsmentioning
confidence: 99%
“…All patients had a molecular diagnosis using established techniques [23][24][25][26][27] or fulfilled the criteria of hmzFH. 23 All patients' charts were reviewed using preestablished criteria. Anthropometric, clinical data, time of diagnosis, initiation of treatment, duration of specific treatments were collected, and all pertinent surgical reports were reviewed.…”
Section: Study Subjectsmentioning
confidence: 99%
“…18 In contrast, the greater likelihood of a positive diagnosis with use of the same screening method (but with relatively low plasma LDL-C thresholds, compared with the diagnostic levels used for screening of the general population) in relatives of patients already known to have HeFH was highly effective: 18 while specificity remained high at 98%, sensitivity improved to 88% for first-degree relatives, 85% for second-and 81% for thirddegree relatives because of the greater likelihood of a positive diagnosis. The authors 18 strongly recommended biochemical screening of relatives of patients found to have HeFH (an approach that has been called cascade testing) 20 over other detection strategies such as population-wide LDL-C testing.…”
Section: Diagnosismentioning
confidence: 99%
“…Both genetic and phenotypic approaches of screening require expertise in working with and giving advice to families [20][21][22][23][24] . Issues such as feeling isolated and anxious on learning about a familial mutation and/or receiving their own results have been reported by at-risk family members 25) .…”
Section: Familial Hyperlipidemia Nurses and Staffmentioning
confidence: 99%
“…. Concerns were raised about general pediatric screening and the psychological impact of an FH diagnoses on children and parents 20,21,96) ; however, evidence has yet to show serious detrimental effects of FH diagnoses in such cases [97][98][99][100][101] . Clearly, a universal screening program would need to be tested and validated in a smaller population with these considerations in mind before it can be used on a more general basis 91) .…”
Section: Rds Declares the Following Relationships For The Last 12 Monmentioning
confidence: 99%